Evidence for an expanding corona based on spectral-timing modelling of multiple black hole X-ray binaries. Issue 2 (27th October 2021) - Cao, Zheng; Lucchini, Matteo; Markoff, Sera; Connors, Riley M T; Grinberg, Victoria
ABSTRACT: Galactic black hole X-ray binaries (BHXBs) provide excellent laboratories to study accretion, as their relatively quick evolution allows us to monitor large changes in the in-flowing and/or out-flowing material over human time-scales. However, the details of how the inflow–outflow coupling evolves during a BHXB outburst remain an area of active debate. In this work, we attempt to probe the physical changes underlying the system evolution, by performing a systematic analysis of the multi-wavelength data of three BHXB sources: XTE J1752-223, MAXI J1659-152, and XTE J1650-500, during hard and hard-intermediate states. Using the power spectral hue which characterizes the X-ray variability properties, we identify several clusters of BHXB epochs and perform the joint multi-wavelength spectral modelling to test their commonality with a physical jet model. Under the assumption that the corona is related to the base of the jet, we find that the power spectral hue traces the variation of the coronal radius (from ∼10 Rg – ∼ 40 Rg ) in multiple BHXBs at hard and hard-intermediate states, and that the data are consistent with moderately truncated accretion discs (<25 Rg ) during hard-intermediate states. We also find that all epochs of low disc reflection have high hue located near the hard-intermediate to soft-intermediate state transition, indicating that in these states the vertical extent of the corona and/or its bulk speed are increasing. Our results link the geometrical similarity in the corona among multiple BHXB sources to their timing characteristics, and probe the corona responding to the disc-jet interactions at hard and intermediate states during outbursts.